2011
DOI: 10.1128/jb.05777-11
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Genomic Analysis of Xanthomonas axonopodis pv. citrumelo F1, Which Causes Citrus Bacterial Spot Disease, and Related Strains Provides Insights into Virulence and Host Specificit

Abstract: Xanthomonas axonopodis pv. citrumelo is a citrus pathogen causing citrus bacterial spot disease that is geographically restricted within the state of Florida. Illumina, 454 sequencing, and optical mapping were used to obtain a complete genome sequence of X. axonopodis pv. citrumelo strain F1, 4.9 Mb in size. The strain lacks plasmids, in contrast to other citrus Xanthomonas pathogens. Phylogenetic analysis revealed that this pathogen is very close to the tomato bacterial spot pathogen X. campestris pv. vesicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0
3

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(55 citation statements)
references
References 112 publications
(109 reference statements)
0
50
0
3
Order By: Relevance
“…A de novo BamHI optical map of the genome of XacA*270 was generated by OpGen Technologies (Madison, WI, USA). The draft genome of XacA*270 was closed using the method described in our previous study (Jalan et al, 2011).…”
Section: Strainsmentioning
confidence: 99%
See 1 more Smart Citation
“…A de novo BamHI optical map of the genome of XacA*270 was generated by OpGen Technologies (Madison, WI, USA). The draft genome of XacA*270 was closed using the method described in our previous study (Jalan et al, 2011).…”
Section: Strainsmentioning
confidence: 99%
“…The reads from XacA and XacA w strains were reference assembled against XacA306 and XacA w 12879 genome (da Silva et al, 2002; Jalan et al, 2013b), respectively. As no XacA* genome was publically available, De Novo assembly was conducted for the genome of XacA*270 (Supplementary Table S2) using previously described methodology (Jalan et al, 2011), and the two remaining XacA* strains were reference assembled based on the XacA*270 genome. The comparison of our reads and assemblies (Supplementary Table S3) with other published assemblies for Xanthomonas (Bart et al, 2012) indicated that our assemblies are of high quality.…”
Section: Genomic Features Of Citrus Canker-causing Xac Strainsmentioning
confidence: 99%
“…3B). In addition to the numerous regulatory loci that map elsewhere in the Xanthomonas genomes (16)(17)(18)(19)(20), our findings highlight the existence of key regulatory loci that map within the hrp-hrc-hpa genes in X. oryzae pv. oryzicola.…”
Section: Discussionmentioning
confidence: 94%
“…In xanthomonads, the hrp-hrc-hpa genes are highly conserved and clustered within several sequenced genomes (16)(17)(18)(19)(20). Our previous studies revealed that the hrp cluster in X. oryzae pv.…”
mentioning
confidence: 99%
“…citrumelonis (X. axonopodis pv. citrumelo), which specifically attacks rootstocks of the 'Swingle' citrumelo (Citrus paradisi x Poncirus trifoliata) [28], and the fifth ortholog was found in X. campestris pv. ve-sicatoria, which causes disease in peppers and tomatoes [29].…”
Section: Mutants Showing Total Loss Of Virulence In C Sinensis and Cmentioning
confidence: 99%